2022
DOI: 10.1002/dev.22232
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent girls’ intrapersonal and interpersonal parasympathetic regulation during peer support is moderated by trait and state co‐rumination

Abstract: Effective emotion regulation (ER) is integral to adolescents’ mental well‐being and socioemotional development. During adolescence, peer interactions have an increasingly salient influence on the development of effective ER, but not all supportive peer interactions support adaptive ER. Co‐rumination reflects the tendency to seek ER support by engaging with peers in negatively focused discussion of ongoing problems. We examined associations between co‐rumination (state and trait) with measures of individual's a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 65 publications
2
10
1
Order By: Relevance
“…One of the novel contributions of this study was the finding that co-rumination suppressed the beneficial effect of seeking support from friends and depression: adolescents who identified they would seek support from their friends reported higher levels of co-rumination, which was in turn was related to higher depression scores. The positive relationship between seeking support from friends and co-rumination is unsurprising, given the extensive body of evidence that connects co-rumination with increases in friendship quality [e.g., ( 7 , 8 )]. Our findings also align with and extend those of Vélez et al ( 15 ), who reported that support seeking was a useful coping strategy for adolescents if they also engaged in low levels of rumination, but that support seeking became problematic in the presence of high levels of rumination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the novel contributions of this study was the finding that co-rumination suppressed the beneficial effect of seeking support from friends and depression: adolescents who identified they would seek support from their friends reported higher levels of co-rumination, which was in turn was related to higher depression scores. The positive relationship between seeking support from friends and co-rumination is unsurprising, given the extensive body of evidence that connects co-rumination with increases in friendship quality [e.g., ( 7 , 8 )]. Our findings also align with and extend those of Vélez et al ( 15 ), who reported that support seeking was a useful coping strategy for adolescents if they also engaged in low levels of rumination, but that support seeking became problematic in the presence of high levels of rumination.…”
Section: Discussionmentioning
confidence: 99%
“…Broader evidence suggests that support seeking is 10.3389/fpsyt.2023.1040636 likely to be maladaptive if it includes co-rumination: the repeated discussion of problems and associated negative affect with close friends (5,6). Co-rumination is particularly common in adolescent girls' friendships and, while it can contribute to stronger friendships (7,8), it also predicts poorer mental health (9,10). It is unknown, however, whether co-rumination influences the relationship between traditional or online support-seeking tendencies and mental health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies investigated associations between adolescent friendships and neural, physiological, and biological markers of health, documenting both short-and long-term associations of adolescent friendships on neural processes (Braams et al, 2014;Braams & Crone, 2017a, 2017bSchreuders et al, 2019Schreuders et al, , 2021Vijayakumar et al, 2020), metabolic control (Helgeson et al, 2007(Helgeson et al, , 2009(Helgeson et al, , 2014, and inflammation (Millwood & Manczak, 2023). One study focused on parasympathetic regulation (i.e., respiratory sinus arrhythmia) (Stone et al, 2021) while others measured the effects of friendships on hypothalamic-pituitary-adrenal (HPA) axis activity and stress levels broadly (Adams et al, 2011;Calhoun et al, 2014Calhoun et al, , 2021Doom et al, 2017).…”
Section: Physiological and Biological Healthmentioning
confidence: 99%
“…Whereas most studies measured cortisol, one cross-sectional behavioral observation study investigated the association between friendship quality and respiratory sinus arrhythmia (RSA). Stone et al (2021) asked 30 female adolescent dyads between the ages of 11-17 to report on their friendship closeness captured by five positive relationship features as well as partake in a peer support task to measure dyadic co-rumination (e.g., rehashing of problems, dwelling on negative affect) and autonomic regulation synchronicity via RSA. Friendship closeness did not significantly predict RSA variation during the task; however, dyadic co-rumination during the peer task no longer predicted RSA synchronicity after accounting for friendship closeness.…”
Section: Physiological and Biological Healthmentioning
confidence: 99%